Status in Socio-Environmental Fields: Relationships, Evaluations, and Otherhood - Nadine Arnold; Fabien Foureault (Emerald Publishing Limited, 2024)
Status distinctions matter among heterogeneous organizations within a socio-environmental field. This is exemplified in the food waste field, where six types of organizations employ different excess strategies to address the issue. Theoretically, we propose that status is constructed internally through advice relationships and externally through evaluations. We posit that organizations conducting evaluations and advocating legitimate principles based on expertise (i.e., Others) are status winners. Our mixed-method study confirms that Others hold privileged positions and identifies status inconsistencies. By critically illuminating these status dynamics, we contribute to a better understanding of the roles of organizations and status in tackling socio-environmental issues.
10.1108/S0733-558X20240000090005; 10.1108/S0733-558X20240000090005; Sociological Thinking in Contemporary Organizational Scholarship; EBP109300890